Prognostic factors associated with mortality and major in-hospital complications in patients with bacteremic pneumococcal pneumonia: Population-based study. Issue 46 (November 2016) - Beatty, Jessica A.; Majumdar, Sumit R.; Tyrrell, Gregory J.; Marrie, Thomas J.; Eurich, Dean T.
Abstract : Abstract: Bacteremic pneumococcal pneumonia (BPP) causes considerable mortality and morbidity. We aimed to identify prognostic factors associated with mortality and major in-hospital complications in BPP. A prospective, population-based clinical registry of 1636 hospitalized adult patients (≥18 years) with BPP was established between 2000 and 2010 in Northern Alberta, Canada. Prognostic factors for mortality and major in-hospital complications (e.g., cardiac events, mechanical ventilation, aspiration) were evaluated using multivariable logistic regression. Average age was 54 (standard deviation 18) years, 57% males, and 59% had high case-fatality rate (CFR) serotypes. Overall, 14% (226/1636) of patients died and 22% (315/1410) of survivors developed at least 1 complication. Independent prognostic factors for mortality were age (adjusted odds ratio [aOR], 1.5 per decade; 95% confidence interval [CI], 1.3–1.7), nursing home residence (aOR, 3.7; 95% CI 1.8–7.4), community-dwelling dementia (aOR 3.7; 95% CI, 1.6–8.6), alcohol abuse (aOR, 2.2; 95% CI, 1.4–3.4), acid-suppressing drugs (aOR, 1.5; 95% CI, 1.0–2.3), guideline-discordant antibiotics (aOR, 3.4; 95% CI, 2.4–4.8), multilobe pneumonia (aOR, 2.6; 95% CI, 1.8–3.6), and high CFR serotypes (aOR, 1.8; 95% CI, 1.2–2.8). Similar prognostic factors were observed for major in-hospital complications. Pneumococcal vaccination was associated with reduced in-hospital mortality (aOR, 0.2; 95% CI, 0.05–0.9) but not major complications ( P = 0.2). Older and frailer patients, and those who abuse alcohol or take acid-suppressing drugs, are at increased risk of BPP-related mortality and complications, as are those with high CFR serotypes. Beyond identifying those at highest risk, our findings demonstrate the importance of guideline-concordant antibiotics and pneumococcal vaccination in those with BPP. Abstract : Supplemental Digital Content is available in the text